Determinación de babesia canis en caninos de la ciudad de Machala provincia de El Oro - Loayza Romero, María de los Ángeles (2014)
The research was conducted in collaboration with the residents of the community of Puerto Bolivar, El Cambio, Jubones, Providence belonging to the city of Machala, El Oro Province, from December of 2013 to February ., 2014 Objectives outlined in the research were: General Purpose, Determination of the prevalence of Babesia canis in the dog population of the city of Machala, El Oro Province Specific Objectives; 1. Determine the prevalence rate of Babesia canis in the dog population of the city of Machala, El Oro Province 2. Determine the prevalence rate varying according to race, sex, age groups and habitat of dogs who have contracted disease. The number of samples collected was 200 from dogs with symptoms of the disease. For sampling proceeded to cut hair, disinfect with alcohol or iodine, a tourniquet was made to gain visibility into the cephalic vein and blood was extracted using syringes 3cm where previously two drops of anticoagulant was placed ( EDTA). Then proceeded to the drying air spontaneously smear fixing it with methyl alcohol for 10 minutes, alcohol was removed and left to dry at ambient, then the dye is placed. We leave the dye on for 20 minutes, then washed and dried and then observed under a microscope with immersion lens. The hemoparasite was identified microscopically in the cytoplasm of the red blood cell, the same as that presented in the form of a pear. The investigation determined Determination of Babesia canis in dogs in the city of Machala, province of El Oro is 90 positive cases is 45%. The prevalence of Babesia canis was higher in male dogs represented by 54 animals given 27% and for females was 36 animals with 18%. The prevalence of Babesia canis according to habitat is 7% home, 22% in patio, terrace and 6.5% in 9.5% of positive cases in street. The Babesia Canis according to race has a higher percentage for large breeds with 18.5%. The Babesia Canis according to age has a greater affinity for young dogs with 23.5%.